2019
DOI: 10.2147/mder.s198220
|View full text |Cite
|
Sign up to set email alerts
|

<p>Technology update: dissolvable microneedle patches for vaccine delivery</p>

Abstract: Despite vaccination representing one of the greatest advances of modern preventative medicine, there remain significant challenges in vaccine distribution, delivery and compliance. Dissolvable microarray patches or dissolving microneedles (DMN) have been proposed as an innovative vaccine delivery platform that could potentially revolutionize vaccine delivery and circumvent many of the challenges faced with current vaccine strategies. DMN, due to their ease of use, lack of elicitation of pain response, self-dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 107 publications
(137 reference statements)
0
54
0
Order By: Relevance
“…prepared in either dissolving or hydrogel-forming formulations. DMN arrays have attracted attention mainly due to their demonstrated ability to efficiently deliver hydrophobic and hydrophilic drugs, vaccines and nanoparticles across the skin (34)(35)(36). On the other hand, HFMN arrays have shown their potential to be used, not only in the delivery of various drug molecules, but also in the extraction of skin interstitial fluid for diagnostic purposes (29,37).…”
Section: Discussionmentioning
confidence: 99%
“…prepared in either dissolving or hydrogel-forming formulations. DMN arrays have attracted attention mainly due to their demonstrated ability to efficiently deliver hydrophobic and hydrophilic drugs, vaccines and nanoparticles across the skin (34)(35)(36). On the other hand, HFMN arrays have shown their potential to be used, not only in the delivery of various drug molecules, but also in the extraction of skin interstitial fluid for diagnostic purposes (29,37).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, microneedle technology has attracted extensive scientific and industrial interests due to its properties including painless penetration, relative safety, and low cost 8 . The postulated widespread applications of microneedle sheets include the delivery of insulin, vaccines, anti-inflammatory substances, and other pharmaceuticals 9 . While microneedle sheets are expected to become a highly efficient, patient-friendly, and versatile device 10 , most purported applications are extracorporeal or an intradermal.…”
Section: Discussionmentioning
confidence: 99%
“…Really, as stated by some published studies, the ability of microorganisms to cross the holes created in the skin by MN insertion seems to be negligible [147]. Some studies have demonstrated that by using solid silicon MNs, the crossing of Candida albicans and Pseudomonas aeruginosa pathogens through cell membranes is lower in comparison with the use of a 21G hypodermic needle [148]. Together with these results, another study performed by Wei-Ze et al [149] reported that rats cured with solid silicon MNs did not become septic by Staphylococcus aureus.…”
Section: Sterilization and Storagementioning
confidence: 99%